The Influence of Visionary Leadership Style, School Climate, and Interpersonal Relationships on Teacher Productivity - Joy Frandero Yoni Astra Pasaribu; Widi Dewi Ruspitasari; Ike Kusdyah Rachmawati (Al-Qalam Institue, 2026)
This study aims to analyze the influence of principals’ visionary leadership style, school climate, and interpersonal relationships on teacher productivity. A quantitative approach was employed using a census method, involving all teachers in the population as respondents. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression with SPSS. The results indicate that, partially, visionary leadership has a positive and significant effect on teacher productivity, while school climate and interpersonal relationships do not show a significant partial effect. However, simultaneously, visionary leadership, school climate, and interpersonal relationships have a significant influence on teacher productivity. The coefficient of determination (R²) of 0.547 indicates that 54.70% of the variance in teacher productivity can be explained by the three independent variables, while the remaining variance is influenced by other factors outside the research model. These findings highlight the critical role of principals’ visionary leadership as the dominant factor in enhancing teacher productivity, as well as the importance of strengthening school climate and interpersonal relationships as supporting factors for sustaining teacher performance in the long term.